(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Anita Desai’s Fasting, Feasting is a novel which clearly projects the consumeristic tendencies and commodification in west as it is perceived by the protagonist Arun. The novel portrays India as a land not yet facilitated by modernity. At the same time Indians are gradually taken to ways of western modernization. Eurocentric notions make a sort of neo-colonization in the minds of the erstwhile colonized people. Avarice and over-indulgence become the key-words of the consumeristic world. Abundance leading to wastage becomes the trend of the west.